Antibiofilm Properties and Demineralization Suppression in Early Enamel Lesions Using Dental Coating Materials - Niraya Kornsombut; Shoji Takenaka; Maki Sotozono; Ryoko Nagata; Takako Ida; Jutharat Manuschai; Rui Saito; Ryouhei Takahashi; Yuichiro Noiri (MDPI AG, 2024)
This study aimed to investigate the effects of dental coating materials on Streptococcus mutans biofilm formation. The test materials were PRG Barrier Coat (PRG), BioCoat Ca (BioC), and FluorDental Jelly (FluorJ). Bovine enamel specimens were demineralized to mimic early enamel lesions. The biofilm was developed on a specimen treated with one of the materials by using a modified Robbins device flow-cell system. Scanning electron and fluorescence confocal laser scanning microscopy, viable and total cell counts, and gene expression assessments of the antibiofilm were performed. Ion incorporation was analyzed using a wavelength-dispersive X-ray spectroscopy electron probe microanalyzer. All materials allowed biofilm formation but reduced its volume. FluorJ was the only material that inhibited biofilm accumulation and had a bactericidal effect, revealing 0.66 log CFU in viable cells and 1.23 log copy reduction in total cells compared with the untreated group after 24 h of incubation. The ions released from PRG varied depending on the element. BioC contributed to enamel remineralization by supplying calcium ions while blocking the acid produced from the biofilm. In summary, the dental coating materials physically prevented acid attacks from the biofilm while providing ions to the enamel to improve its mechanical properties.